Deep Cuba : The Inside Story of an American Oceanographic Expedition - Belleville, Bill, 1945- (Book collections on Project MUSE., 2002)
Geography, politics, and other factors have allowed Cuba to preserve the region's most pristine coast and offshore marine environment. Deep Cuba recounts Bill Belleville's month-long journey around the island in the company of American and Cuban marine biologists and a Discovery Channel film crew. It was the first, and so far only, United States submersible research expedition in Cuban waters. From coral reefs to mangrove swamps to a submerged volcanic mountain, the voyagers encountered sublimely wild places unseen before by anyone from the United States--or even by many Cubans. Belleville conveys the tempo of the scientists' workday, during which the routine gathering of data and specimens could be punctuated by trips in a state-of-the-art submersible, the discovery of new species, or a tropical storm. Throughout the trip, as well, all on board had to work through differences that arose from the expedition's contrary goals: to produce a commercially viable seagoing adventure film and to conduct controlled, methodical scientific investigations. Belleville paces his coverage of the expedition with absorbing stories about the history and culture of the island's peoples, from the indigenous Taino to its current inhabitants of African and European heritage. Deep Cuba even includes a candid portrait of Castro himself. An avid diver, sport fisherman, and naturalist, El Comandante paid a visit aboard the research vessel. Deep Cuba is an engaging mix of nature and travel writing, along with scientific reportage that is keenly attuned to current crises in research funding. Revealed here is a magnificent marine world with crucial ecological links to the Caribbean Basin and the southeastern United States.